KEPUASAN KERJA PEREMPUAN PETUGAS KEBERSIHAN DI UNIVERSITAS RIAU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the job satisfaction of women cleaningworkers at the University of Riau, so the aim is to determine the level of job satisfactionof women janitors at the University of Riau. This research is descriptive with aquantitative approach which aims to describe the results of the study with numbers. Thesample of this study using the sampling technique in this study is the simple randomsampling technique (simple random sampling). The data collection technique in thisstudy was a questionnaire technique, which amounted to 48 statements. Data obtainedfrom respondents, amounting to 71 female cleaners for the study sample and 29 femalecleaners for trials. After the questionnaire was tested, there were 5 invalid items, andthe researcher discarded all that were invalid. So that the whole instrument is declaredreliable with Cronbach's Alpha = 0.976 with the number of items 43 statements. Basedon the results of the study, the job satisfaction variable of women cleaning workers atthe University of Riau is quite high, seen from the mean value of 3.96 and SD 0.77which are in a fairly high position of interpretation. As well as job satisfaction ofwomen cleaning workers at the University of Riau, the highest is the emotional state ofwork and suitability for work with a mean number of 4.03. This means that womencleaning services are satisfied with their work, which is shown by a good emotionalsense of their work and a sense of conformity with their work, because of the skills theyhave in cleaning.Key Words: Job Satisfaction, Job Satisfaction of Women Cleaning Workers